Spinal Antinociceptive Action of Amiloride and Its Interaction with Tizanidine in the Rat Formalin Test - Handong Ouyang; Peizong Wang; Wan Huang; Qiang Li; Bilin Nie; Weian Zeng (Pain Research and Management)
BACKGROUND: Amiloride has been reported to produce a wide variety of actions, thereby affecting several ionic channels and a multitude of receptors and enzymes. Intrathecal α2-adrenergic receptor agonists produce pronounced analgesia, and amiloride modulates α2-adrenergic receptor agonist binding and function, acting via the allosteric site on the α2A-adrenergic receptor.